Characterising intra- and inter-intrinsic network synchrony in combat-related post-traumatic stress disorder. Issue 2 (30th November 2015) - Dunkley, Benjamin T.; Doesburg, Sam M.; Jetly, Rakesh; Sedge, Paul A.; Pang, Elizabeth W.; Taylor, Margot J.
Abstract: Soldiers with post-traumatic stress disorder (PTSD) exhibit elevated gamma-band synchrony in left fronto-temporal cortex, and connectivity measures in these regions correlate with comorbidities and PTSD severity, which suggests increased gamma synchrony is related to symptomology. However, little is known about the role of intrinsic, phase-synchronised networks in the disorder. Using magnetoencephalography (MEG), we characterised spectral connectivity in the default-mode, salience, visual, and attention networks during resting-state in a PTSD population and a trauma-exposed control group. Intrinsic network connectivity was examined in canonical frequency bands. We observed increased inter-network synchronisation in the PTSD group compared with controls in the gamma (30–80 Hz) and high-gamma range (80–150 Hz). Analyses of connectivity and symptomology revealed that PTSD severity was positively associated with beta synchrony in the ventral-attention-to-salience networks, and gamma synchrony within the salience network, but also negatively correlated with beta synchrony within the visual network. These novel results show that frequency-specific, network-level atypicalities may reflect trauma-related alterations of ongoing functional connectivity, and correlations of beta synchrony in attentional-to-salience and visual networks with PTSD severity suggest complicated network interactions mediate symptoms. These results contribute to accumulating evidence that PTSD is a complicated network-based disorder expressed as altered neural interactions. Highlights: Increased intrinsic inter-network synchronisation in PTSD compared with controls. PTSD severity was associated with synchrony within and between a number of networks. Network atypicalities may reflect trauma-related alterations to connectivity. Evidence suggests PTSD is a network disorder expressed as altered neural interactions.